Влияние начальных параметров на характеристики проточных частей турбин, работающих на низкокипящих рабочих телах - Шубенко, Александр Леонидович; Сенецкий, Александр Владимирович; Сарапин, Владимир Павлович (НТУ "ХПИ", 2016)
Приведены результаты расчетных исследований с использованием программного комплекса, разработанного в ИПМаш НАН Украины, по определению расходных и геометрических характеристик проточных частей турбин на органических рабочих телах, с учетом их свойств. Проведен сравнительный анализ характеристик проточных части турбин со сверхкритическими и докритическими параметрами рабочего тела на входе в турбину. Показано влияние начальных параметров на экономичность и мощность турбины.

A comparative analysis of supercritical and subcritical steam turbine cycles with low-boiling actuating medium has been done. The effect of initial steam parameters at the turbine inlet on the metering, geometric and power characteristics of the turbine was demonstrated using different actuating media. Steam turbine cycles of this type using the mix (multicomponent) medium or single-component actuating medium that define the amount of capital expenditures and have an impact on the further operation of heat flow diagram have also been compared. Computation studies of the flow system of turbines using different actuating media were carried out taking into consideration the thermodynamic properties and peculiarities of low-boiling actuating media in question.
Influence of initial parameters on the performances of the flow system of turbines operating on low-boiling actuating medium
Keywords: электрическая мощность; энергосбережение; тепловая схема; electric power; energy saving; heat flow diagram